1998
DOI: 10.1073/pnas.95.23.13561
|View full text |Cite
|
Sign up to set email alerts
|

A 55-kDa protein isolated from human cells shows DNA glycosylase activity toward 3, N 4 -ethenocytosine and the G/T mismatch

Abstract: Etheno adducts in DNA arise from multiple endogenous and exogenous sources. Of these adducts we have reported that, 1,N 6 -ethenoadenine (A) and 3,N 4 -ethenocytosine (C) are removed from DNA by two separate DNA glycosylases. We later confirmed these results by using a gene knockout mouse lacking alkylpurine-DNA-N-glycosylase, which excises A. The present work is directed toward identifying and purifying the human glycosylase activity releasing C. HeLa cells were subjected to multiple steps of column chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 45 publications
0
74
0
Order By: Relevance
“…(36,48,72,76) Overlap between glycosylases is also common as examplified by the in vitro identification of the eC-activity in three human DNA glycosylase, TDG, SMUG1 and MBD4. (52,(54)(55)(56) Although the biological function of these activities remains to be seen, such redundancy of repair is expected to be useful for backing up in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(36,48,72,76) Overlap between glycosylases is also common as examplified by the in vitro identification of the eC-activity in three human DNA glycosylase, TDG, SMUG1 and MBD4. (52,(54)(55)(56) Although the biological function of these activities remains to be seen, such redundancy of repair is expected to be useful for backing up in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…(51) Through an extensive purification, the eC-DNA glycosylase was identified as a 55 kDa polypeptide by SDS-PAGE, (52) which is the exact molecular mass of the previously purified human mismatchspecific T(U) Á G-DNA glycosylase, termed thymine-DNA glycosylase (TDG). (53) Moreover, the T Á G and U Á G mismatch glycosylase activities co-eluted with the eC activity in the same fractions, and competition studies suggested that they all reside in the same protein.…”
Section: Excision Of Ecmentioning
confidence: 99%
See 3 more Smart Citations